Post a New Question

maths

posted by .

if the ratio of the roots of the equation ax2+bx+c is m:n

  • maths -

    What is your question?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. maths

    Show that the equation (1) divided by (x+1) - (x)divided by (x-2)=0 has no real roots Well, to begin, start with 1/(x+1-x). The x's cancel out because they are opposite signs, so now you have 1/1, or just 1. Then, you are dividing …
  2. maths

    find the roots of the equation X(square)+7x equal to 0.(b)write down the equation whose roots are -2 and 5. I will be happy to critique your thinking. Write the equation, and solve. In the second, hint: (x+2) is one factor.
  3. Maths

    Write down the equation whose roots are: i) two more than ii) the square of iii) three times as much as the roots of the equation 4x^2-x+2=0
  4. maths

    If 5x4-14x³+18x²+40x+16=(x²-4x+8)(ax²+bc+c) find a,b and c and hence find the four solutions of the equation 5x4-14x³+18x²+40x+16 Given that x³-1=(x-&)(ax²+bx+c) find the values of a,b and c and hence find the three roots of …
  5. Math (Algebra)

    If the ratio of the roots of the quadratic equation x^2−28x+A=0 is 2:5, what is the product of the roots of the quadratic equation x^2+Ax+2A+3=0?
  6. maths

    If the ratio of the roots of the quadratic equation ax^2 + bx +c =0 is m:n prove that mnb^2=(m+n)^2 ac
  7. maths

    If one of the roots of the eqn ax²+bx+c=0 be reciprocal of one of the roots of a1x²+b1x+c1=0 then prove that (a a1-c c1)²=(b c1-a b1)(b1 c- a1 b)
  8. maths-equadratic eqn

    one of the roots of the quadratic equation x^2-(4+k)x+12=0 find, 1)the roots of the equation 2)the possible values of k please show your workings thanks in advance.
  9. maths

    Solve the quadratic equation ax2+bx+c=0 using the completing the squares
  10. precalculus

    can you please check my work? 7. Find the equation of the parabola y=ax2+bx+c that passes through the points(0,6),(-2,2), and(3,9/2). y=ax2+bx+c 6=a(0)2+b(0)+c 2=a(-2)2+b(-2)+c 9/2=a(3)2+b(3)+c 6=c 2=4a+(-2b)+6 9/2=9a+3b+6 -4=4a-2b

More Similar Questions

Post a New Question